The The Effect Capital Structure , Efficiency Operations , Non - interest Income To Profitability on Banking Companies Listed on the Indonesia Stock Exchange (IDX): Financial Management Studies - Cici Maharani; Aimatul Yumna (Financial Management Studies, 2023)
Study this aim for analyze the effect of (1) Capital Structure on profitability , (2) Efficiency Operation to Profitability , (3) Non - interest income to Profitability listed on the Indonesia Stock Exchange in 2017-2021. Study this use one control variable : size company . Population in study this is whole company banking listed on the Indonesia Stock Exchange . Whereas sample in study this determined with purposive sampling method , ie sample company banking for five years consecutive from years 2017-2021, so obtained dsum sample as many as 35 companies with observational data 159 for every variable . Method analysis use analysis regression double with using the IBM SPSS Statistics 23 program. Research results this conclude that (1) the effect capital structure negative significant to profitability company banking listed on the Indonesia Stock Exchange , (2) The effect Efficiency Operation negative significant with profitability company banks listed on the Indonesia Stock Exchange , and (3)The effect Non - interest income positive significant to profitability company banking listed on the Indonesia Stock Exchange .